2018
DOI: 10.1177/0192513x18777867
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Parent: The Targeted Parent Perspective of Parental Alienation

Abstract: This study investigated the targeted parent experience of parental alienation and alienating behaviors. One hundred and twenty-six targeted parents provided narratives in response to an open-ended question at the end of an online survey. Braun and Clarke’s (2006) thematic analysis framework was used to identify themes in the data. Six themes were identified illustrating targeted parents’ experience of parental alienation and alienating behaviors. Targeted parents described physical and emotional distance separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 53 publications
4
44
0
9
Order By: Relevance
“…First, some authors found more mothers participated in their research than was expected (Baker & Darnall, ; Balmer et al, ; Poustie et al, ), which would suggest that perhaps in previous studies the voluntary participation rate of fathers was higher. Second, past recruitment processes may have influenced the gender recruited.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…First, some authors found more mothers participated in their research than was expected (Baker & Darnall, ; Balmer et al, ; Poustie et al, ), which would suggest that perhaps in previous studies the voluntary participation rate of fathers was higher. Second, past recruitment processes may have influenced the gender recruited.…”
Section: Discussionmentioning
confidence: 86%
“…As shown in Table , six of the studies included more males than females in the sample. One article (Finzi‐Dottan et al, ) included only females as a result of purposive sampling, and two other studies (Balmer et al, ; Poustie et al, ) had more females than males participating in the research. The studies were conducted mostly in the United States (six articles), two in Australia and one in Israel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations